Housing development and consumer protection: a study on the problems of late delivery of vacant possession - Amin, Naemah; Kassim, Salina; Syed Abdul Kader, Sharifah Zubaidah (2015)
One of the main duties of the housing developer in Malaysia is to complete the construction of the house on time. Schedules G and H of the Housing Development (Control and Licensing) Act 1966 provides that the period of completion and handling over vacant possession for landed property is 24 months and for sub-divided building is 36 months. However in practice, some buyers did not get the keys to their houses on time as a delay in completion of project has become common phenomenon in the housing industry. Unlike other construction projects, any problems with the housing project will affect many people due to the significant nature of housing project to public at large. A delay in delivering the house to the anxious buyer may mean delaying his right to one of human basic needs. A late delivery may also cause financial, social and emotional problems to the buyers just like abandoned projects but perhaps with a lesser degree of hardship since they eventually got the keys to the house. Adopting a combination of qualitative and quantitative research methodology, this study aims to identify the actual causes of late delivery of residential houses and its effect on the consumers as well as to examine the adequacy of law and housing policy in Malaysia in ensuring the residential houses are completed on time. The study also explores house buyers’ experiences with regard to the problems of late delivery, including various issues and challenges faced by them in claiming damages for late delivery of vacant possession. The findings revealed that lack of enforcement of housing law and policy as one of the contributing factors of project delay and the house buyers are not adequately protected under the existing law and practices. Ultimately, the study provides insights to practitioners and policy makers on further improvements of the law and policy to minimize or prevent the delay in completing the housing project as well as to protect house buyers’ interests in the case of late delivery of vacant possession in the housing market in Malaysia. Undeniably the issue of late and delay is a reflection of inefficiency in the housing industry. It has a negative implication on business reputation of all parties involved in the construction industry – developers, contractors, consultants etc. But the ultimate victim of delay is the end-user of the construction product, i.e. the purchaser. It is thus a fair and reasonable principle of law that the victim of late delivery of vacant possession should be awarded with automatic and fixed calculation of compensation. Under the existing housing law and policy, all relevant bodies and agencies have been conferred with wide and adequate power to ensure timely completion of housing projects. However to what extent this power has been exercised in favour of house buyers is highly questionable. It can safely be said that the main concern of house buyer protection in Malaysia right now is not so much whether there is adequate legal protection, but more on the issues of implementation and enforcement. The problem will hopefully be solved or minimized with full implementation of ‘build then sell’ scheme in the near future.